Contributions of Look Duration and Gaze Shift Patterns to Infants' Novelty Preferences. (31st August 2016) - Fisher‐Thompson, Donna
Abstract : Data from 72 infants, tested using a serial paired‐comparison paradigm, were analyzed to better understand infant novelty preferences. Infants between the ages of 15 and 26 weeks were tested in three studies with familiar stimuli displayed adjacent to novel stimuli on each trial. Differences in look duration, look number, and gaze shifts directed at novel versus familiar stimuli were assessed to measure their contributions to group and individual novelty preferences. Infants produced longer looks for novel stimuli in all three studies, and stimulus differences in look duration accounted for more than 50% of the variability in individual novelty preferences. Infants that produced more looks to novel rather than familiar stimuli did not produce overall novelty preferences unless they also looked longer at novel stimuli. Gaze shift patterns did not predict individual novelty preferences, and novel stimuli did not determine where infants looked. The infants' visual exploration was constrained by memories for the direction of the previous look as well as by the attention‐holding features of novel stimuli.